1995
DOI: 10.1111/j.1365-3024.1995.tb00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐gamma and the induction of protective lgG2a antibodies in non‐lethal Plasmodium berghei infections of mice

Abstract: Mice treated with anti-IFN-gamma monoclonal antibodies were unable to recover from infection with an attenuated variant of P. berghei (Pb XAT) which causes non-lethal malaria in normal mice. On the other hand, treatment with anti-IL-4 monoclonal antibodies had no effect on the course of infection. IFN-gamma was produced by spleen cells in vitro during the early phase of the infection. Treatment with anti-IFN-gamma suppressed development of an anti-plasmodial IgG2a immunoglobulin isotype in the serum of infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 17 publications
5
23
2
Order By: Relevance
“…The authors concluded that Th1-associated rise in endogenous TNF-α in the spleen correlates with nonlethal infection. However, contrary to present results, Waki et al (1995) have shown that IL-12 is implicated in pathogenesis instead of providing protection during lethal P. berghei NK65 infection which might be due to the difference in quantity produced, the site of its production, time during which its production is sustained, and presence of other molecules regulating its production. Unlike the Th1 cytokines, Th2 cytokines (IL-10 and IL-4) are known to suppress or downregulate inflammatory responses which are essential to control immune pathology.…”
Section: Nd Ndcontrasting
confidence: 83%
“…The authors concluded that Th1-associated rise in endogenous TNF-α in the spleen correlates with nonlethal infection. However, contrary to present results, Waki et al (1995) have shown that IL-12 is implicated in pathogenesis instead of providing protection during lethal P. berghei NK65 infection which might be due to the difference in quantity produced, the site of its production, time during which its production is sustained, and presence of other molecules regulating its production. Unlike the Th1 cytokines, Th2 cytokines (IL-10 and IL-4) are known to suppress or downregulate inflammatory responses which are essential to control immune pathology.…”
Section: Nd Ndcontrasting
confidence: 83%
“…IFN-γ plays a protective role in malaria infection by inducing the activation of macrophages, which are responsible for the clearance of merozoites and parasitic erythrocytes (Yoneto et al, 2001; Su et al, 2002). It also drives humoral immunity by enhancing IgG2a production, as well as supporting cellular immunity (Waki et al, 1995). Our findings additionally indicate that IFN-γ-independent protective mechanisms successfully control mild parasitemia with PyNL observed in GKO mice, as some or even all GKO mice survived the infection (Figures 1A, 3A).…”
Section: Discussionmentioning
confidence: 99%
“…IgG2a subclass prefers to bind Fc␥RI and then mediate antibody-dependent cell-mediated cellular cytotoxicity, antibody-dependent cellular inhibition, and phagocytosis, but the MSP1 19 -specific IgG2a antibody has been reported not to use the Fc function for antibody-mediated protection (21,27). It may function by blocking parasite invasion or inhibiting MSP1 processing, which is required for erythrocyte entry (3,28).…”
Section: Discussionmentioning
confidence: 99%